2021
DOI: 10.19080/jhnss.2021.04.555637
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Dexamethasone in the Era of “Dex-CSDH” Randomized Controlled Trial. A Multicenter, Prospective Study on Specific Subset of Patients with Chronic Subdural Hematoma (CSDH) Treated with Dexamethasone Alone or Surgery

Abstract: Background:The efficacy of Dexamethasone as a method of conservative management for CSDH to avoid surgery remains inconclusive even after "Dex-CSDH" randomized controlled trial as almost all patients underwent an initial operation to remove the hematoma. Current study aims to determine the efficacy and safety of Dexamethasone alone therapy in comparison with the surgical drain of CSDH. Methods:A multicenter, prospective study on mild to moderately symptomatic adult patients with CSDH were performed from Januar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Dexamethasone has also been shown to reduce the occurrence of repeat surgery after BC for CSDH in randomized control trials; however, not only was it not associated with improved outcomes on the modified Rankin scale at 6 months postsurgery, but it was instead associated with deterioratation. 9,10 It has also been suggested that the adverse effects of dexamethasone has a negative effect on outcomes. 9,10 Atorvastatin has also been reported to be an effective nonsurgical treatment for CSDH 11,12 ; however, there are concerns about the side effects of administering large doses of atorvastatin to the elderly, who typically have reduced hepatic and renal function.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Dexamethasone has also been shown to reduce the occurrence of repeat surgery after BC for CSDH in randomized control trials; however, not only was it not associated with improved outcomes on the modified Rankin scale at 6 months postsurgery, but it was instead associated with deterioratation. 9,10 It has also been suggested that the adverse effects of dexamethasone has a negative effect on outcomes. 9,10 Atorvastatin has also been reported to be an effective nonsurgical treatment for CSDH 11,12 ; however, there are concerns about the side effects of administering large doses of atorvastatin to the elderly, who typically have reduced hepatic and renal function.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 It has also been suggested that the adverse effects of dexamethasone has a negative effect on outcomes. 9,10 Atorvastatin has also been reported to be an effective nonsurgical treatment for CSDH 11,12 ; however, there are concerns about the side effects of administering large doses of atorvastatin to the elderly, who typically have reduced hepatic and renal function. Interaction between atorvastatin and CYP 4A3 is also a concern.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations